Understanding the Psychosocial Roots of Adolescent Self-Harm: Findings from a Descriptive Cross-Sectional Study in Indonesia - Ike Mardianti Agustin; Tri Sumarsih; Irmawan Andri; Siti Mutoharoh (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Self-harm or torturing oneself by intentionally injuring or cutting which is done to relieve the suffering felt. Self-harm behavior is often done by teenagers who are followed by mental health disorders such as symptoms of depression and anxiety. The purpose of this research analyzing predisposing factors of self-harm in adolescence at SMA N 1 Pejagoan. Methods: This study employed a quantitative research using descriptive analytic method with cross sectional approach, sampling using proportional random sampling. The number of samples in this study were 285 adolescents at SMA N 1 Pejagoan. Using 2 questionnaires to determine self-harm behavior using (self-harm inventory instrument) and to determine predisposing factors of self-harm using a predisposing factor screening instrument which has been declared valid, The validity tests indicated that all variables were statistically significant with P-values of <0.001, confirming that the instruments accurately measured their respective constructs and reliable was assessed using Cronbach’s alpha with p-value 0.769 and 0.784. Data analysis using Descriptive statistics were applied for univariate analysis to summarize demographic characteristics and study variables. Results: The results of this study were 271 (95.1%) respondents included in the Self-Harm Group and 14 (4.9%) respondents included in the non Self-Harm group. The majority of predisposing factors causing self-harm behavior were biological with a low category of 138 (48.4%) respondents, for psychological factors the majority were in the medium category of 186 respondents (65.3%) and for socio-cultural predisposing factors the majority were in the low category of 209 (73.3%) respondents. Conclusion: The majority of teenagers are in the self-harm group as many as 271 (95.2%). The biological predisposition factors are mostly in the low risk category as many as 138 (48.4%) respondents, the psychological factors are mostly in the medium risk category as many as 186 (65.3%) respondents and the socio-cultural predisposition factors are mostly in the low category as many as 209 (73.3%) respondents. The results of this study are expected to be a reference material for the need to include mental health material in the school curriculum and recommend further research on the analysis of screening factors predisposing to self-harm in adolescents at SMA N 1 Pejagoan.